Promotion strategies by Malaysian Cocoa Board and the awareness of public communities about cocoa products / Mohammad Hafizullah Muda - Muda, Mohammad Hafizullah (2006)
The purpose of this study was to analyze the level of awareness among public community who lived in Kota Kinabalu district. The study also measured on how much the promotion strategies conducted by Malaysian Cocoa Board would affecting the level of awareness of the community towards the benefits of cocoa. The study was conducted among 150 respondents at chosen area in Kota Kinabalu such as shopping complexes and Indah Permai, Menggatal. The finding in this study has showed that there were a small group of community who still believed that chocolate was not a healthy food. Apart of the community agreed that chocolate provide nutrition to body and some of them were not familiar with the promotion activities conducted by Malaysian Cocoa Board. Exhibition, seminar, TV programme and commercial, publication and attractive figure might help Malaysian Cocoa Board to increase the awareness of community about the benefits and goodness of cocoa.